Educational Outreach on the Use of Gandarusa Leaves (Justicia gendarussa Burm.f.) as a Family Medicinal Plant for Gastrointestinal Health in Tanjungbalai City - Yulia Kusumanti; Indriati Aulia; Wahidah Wahidah; Indah Al Maidah (FKM UIN Sumatera Utara Medan, 2026)
Gastrointestinal disorders remain one of the most common health problems in the community, while the utilization of Family Medicinal Plants (TOGA), particularly Justicia gendarussa Burm.f. (gandarusa) leaves, as a promotive and preventive health approach is still limited due to inadequate public knowledge. This community service program aimed to improve community knowledge regarding the utilization of gandarusa leaves to support gastrointestinal health through TOGA-based health education. A pre-experimental study with a one-group pretest–posttest design was employed. The program was conducted in Teluk Nibung Village, Tanjungbalai City, North Sumatra, involving 100 participants selected using purposive sampling. The educational intervention consisted of interactive lectures, group discussions, demonstrations on the preparation of gandarusa herbal remedies, and the distribution of educational leaflets. Data were collected using knowledge questionnaires administered before and after the intervention and analyzed descriptively using the paired sample t-test. The findings demonstrated a substantial improvement in participants' knowledge, with the proportion of respondents categorized as having good knowledge increasing from 12.0% to 82.0%, while the poor knowledge category decreased from 32.0% to 0.0%. The mean knowledge score significantly increased from 58.6 ± 10.4 before the intervention to 86.8 ± 8.1 after the intervention, with a mean difference of 28.2 points (p < 0.001). Participant engagement was also exceptionally high, as all participants completed the registration, pretest, educational sessions, and posttest. TOGA-based health education proved effective in enhancing community knowledge regarding the utilization of Justicia gendarussa Burm.f. leaves to support gastrointestinal health. This program is recommended for sustainable implementation to strengthen community empowerment and promote the evidence-based use of local medicinal plants.